Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XX): Reduction of D. ellipticovatum and D. tianshanicum to the synonymy of D. winklerianum - Li, Hui-Min; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2019)
Delphinium ellipticovatum, D. tianshanicum and D. winklerianum (Ranunculaceae) share some important characters in leaf division, pedicel pubescence and the shape of the spur of upper sepals. They have been considered to be different mainly in the characters of bracteoles (shape, size, indumentum, and position on pedicels). Our critical observations on herbarium specimens (including type material) and living plants, together with numerical analyses of the bracteole characters within and between populations of the species in question, have demonstrated that, in addition to D. kuanii previously already synonymized with D. winklerianum, both D. ellipticovatum and D. tianshanicum are also indistinguishable from D. winklerianum. We therefore further place D. ellipticovatum and D. tianshanicum also in synonymy with D. winklerianum.